Towards Sustainable Rice Production in Asia: The Role of Climatic Factors - Chandio, Abbas Ali; Gokmenoglu, Korhan K.; Ahmad, Munir; Jiang, Yuansheng (Springer Int Publ Ag, 2022)
This empirical work aims to investigate the long-run impact of climatic factors (i.e., CO2 emissions, precipitation, and temperature), and non-climatic factors (i.e., cultivated area, fertilizer consumption, and rural labor force) on rice production in selected major Asian rice-producing countries over the period 1961-2016. The results of the heterogeneous panel cointegration test show the existence of a long-term equilibrium relationship among the variables. The results of DOLS reveal that climatic factors such as CO2 emissions and temperature significantly reduced rice production in the long-run, while precipitation increased rice production in the long-run. Further findings show that non-climatic factors including cultivated area, fertilizer consumption, and rural labor force significantly enhanced rice production in the long run. It is evident from the findings that precipitation and production factors such as cultivated area, fertilizer consumption, and rural labor force played a vital role in increasing rice production and secure food security in major Asian rice-producing countries. Based on the present findings, this study suggests that to reduce the adverse effects of climate change and ensure food security, there is a need to improve adaptation strategies.
Keywords: Rice production; Climate change; Panel cointegration; Asia